Contribution of silicon fertilizer to soil and growth of Pak choi under reclaimed and brackish water cycling irrigation - Jieru Zhao; Bingjian Cui; Juan Wang; Qibiao Han; Chao Hu; Rui Li; Chuncheng Liu (PLoS ONE, 2025)
Rational utilization and improvement of agricultural water resources has been and is still the focus of research on developing efficient and green agriculture in various countries. Thus, the exploitation and usage of non-traditional water resources hold substantial significance in water resources management and sustainable agriculture. However, their reuse may induce secondary soil salinization and impose stress on crops. To address the challenges of soil salinity and plant stress under brackish-reclaimed water irrigation, this study aimed to investigate the effects of silicon (Si) fertilizer application on soil properties and Pak choi (Brassica rapa L.) performance under two cycling irrigation sequences (RW-BW and RW-RW-BW) and three spraying frequencies (0-, 2-, and 4-day intervals). The findings displayed that the pH of each treatment (7.95-8.10) remained below 8.5, suggesting no risk of secondary soil alkalization. At the same spraying frequency of silicon fertilizer, the soil electrical conductivity (EC) significantly decreased with increasing irrigation times of reclaimed water. Silicon fertilizer improved soil structure and reduced sodium levels, alleviating salinity. The increasing spraying interval of silicon fertilizer provoked the diminution of the SAR and ESP, before rising again. But they were far below the threshold range, and there was no risk of soil salinization (15% and 13 mM1/2). The total silicon content of the soil and leaves increased under the different cycling irrigation conditions. Spraying silicon fertilizer on the crop leaf surface did not significantly influence the total silicon content of the soil. In conclusion, the application of Si-fertilizer beneficially impacts soil physicochemical properties and crop development and mitigates the risk of secondary salinization under brackish-reclaimed water for cycling irrigation.